Розрахунок: DKF1Kj - 1

 
 (y-y1)
/ (y2-y1)
  = 
 
 (x-x1)
/ (x2-x1)
 
 (y-y1)
/ (y2-y1)
 =  
 (x-x1)
/ (x2-x1)
 = 
 
 (y-y1)
/ (y2-y1)
 =  
 x
/ (x2-x1)
- 
 x1
/ (x2-x1)
 = 
(y-y1) =  ( 
 x
/ (x2-x1)
- 
 x1
/ (x2-x1)
)
* (y2-y1)
 = 
y-y1 =  ( 
 x
/ (x2-x1)
- 
 x1
/ (x2-x1)
)
* (y2-y1)
 = 
y =  ( 
 x
/ (x2-x1)
- 
 x1
/ (x2-x1)
)
* (y2-y1)
+y1
 = 
y =  
 y2* x
/ (x2-x1)
- 
 y2* x1
/ (x2-x1)
- 
 y1* x
/ (x2-x1)
+ 
 y1* x1
/ (x2-x1)
+y1
 = 
y =  
 x* y2
/ (x2-x1)
- 
 x1* y2
/ (x2-x1)
- 
 x* y1
/ (x2-x1)
+ 
 x1* y1
/ (x2-x1)
+y1
 =